Reflections on the concepts of "politics," public policy and education policy Reflexiones sobre los conceptos de "política", políticas públicas y política educacional. - Oscar Espinoza (Arizona State University, 2009)
The purpose of this article is to shed light on three key issues: a) the concepts of policy, public policy and educational policy and the interrelations that those concepts have when conducting policy analysis; b) some procedures to conduct policy analysis; and c) some trends observed during the development of educational policies based on the assumptions of critical theory and functionalist theory. Methodologically, this is a qualitative study which uses secondary sources (based on in depth literature review). The study concludes that the design and the implementation of educational policies are framed in different ways by policy makers and other stakeholders adopting the critical and the functionalist paradigm. Policy makers using critical theory as their main framework emphasize the necessity of linking the analysis, design and implementation of educational policies to the demands of those actors that usually are not the target of public policies, that is, poor people and minorities. On the other hand, policy makers that work with functionalist-positivist frameworks use to consider in their analyses technical factors, privileging in that sense, cost-benefit analysis, cost-efficiency analysis, and social indicators. EEl propósito de este artículo es proveer una mirada crítica en relación a tres aspectos: a) los conceptos de "política", políticas públicas y política educacional y las interrelaciones que tienen éstos al momento de conducirse el análisis de políticas; b) algunos procedimientos para conducir el análisis de políticas; y c) algunas tendencias observables en el campo de los procesos de desarrollo e implementación de políticas educacionales a partir de los fundamentos y supuestos que dan sustento tanto a la teoría crítica como al paradigma funcionalista-positivista. Metodológicamente, el estudio es de naturaleza cualitativa de carácter descriptivo-analítico y emplea fuentes secundarias de tipo documental. Tras un exhaustivo análisis de la literatura existente es posible concluir que tanto el diseño como la implementación de políticas educacionales son concebidos de manera muy distinta por los cultores de la teoría crítica y la teoría funcionalista. Mientras los primeros enfatizan la necesidad de vincular inevitablemente el análisis, el diseño e implementación de políticas educativas a las demandas de los sectores más desposeídos de la sociedad en orden a conseguir mayor justicia social y equidad, los segundos argumentan que es imprescindible considerar fundamentalmente factores de carácter técnico, privilegiando, en tal sentido, los análisis de costo-beneficio, costo-eficiencia, costo-efectividad, e indicadores sociales.